1993
DOI: 10.1007/bf00010551
|View full text |Cite
|
Sign up to set email alerts
|

Maize nodal root ramification: Absence of dormant primordia, root classification using histological parameters and consequences on sap conduction

Abstract: A b s t r a c tMaize plants grown in field conditions were used to describe the histological organisation of the nodal roots, those of their laterals, and also to test the presence of critical stages where the subsequent capability for growth and development of young laterals was determined irreversibly. The absence of undeveloped primordia, which stop their development before boring through the nodal mother-root epidermis, proved that the number of laterals could not be regulated between the differentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…However, Green and Clothier (1995) studied water extraction of kiwifruit vines and observed that root water uptake was more dependent on soil water availability than of thin roots distribution. Yet, there are other studies indicating that the diameter of lateral roots was also a highly variable factor in the soil (Yorke and Sagar, 1970;Cahn et al, 1989;Varney et al, 1993;Jordan et al, 1993;Thaler and Pagès, 1996). In addition, Lecompte et al (2005) report that this variability was a consequence of factors like soil heterogeneity, root system structure, and availability and partitioning of carbon in the roots, but the relative contribution of each of these factors remain largely unknown.…”
Section: Recommendations For Sensor Positioning Within the Effective mentioning
confidence: 94%
“…However, Green and Clothier (1995) studied water extraction of kiwifruit vines and observed that root water uptake was more dependent on soil water availability than of thin roots distribution. Yet, there are other studies indicating that the diameter of lateral roots was also a highly variable factor in the soil (Yorke and Sagar, 1970;Cahn et al, 1989;Varney et al, 1993;Jordan et al, 1993;Thaler and Pagès, 1996). In addition, Lecompte et al (2005) report that this variability was a consequence of factors like soil heterogeneity, root system structure, and availability and partitioning of carbon in the roots, but the relative contribution of each of these factors remain largely unknown.…”
Section: Recommendations For Sensor Positioning Within the Effective mentioning
confidence: 94%
“…These tend to optimize the ratio of root length (and hence root surface area for uptake) to root weight (investment). However, decreased root diameter limits root penetration through the soil (Materechera et al, 1992;Clark et al, 2008), and roots must also develop internal structures dedicated to water and nutrient transport (Jordan et al, 1993;Jaramillo et al, 2013). From a developmental point of view, apical diameter reflects the size of the apical meristem.…”
Section: Introductionmentioning
confidence: 99%
“…On maize partic-ularly, the water and mineral transfer resistances are better identified (McCully and Canny, 1988;Peterson et al, 1993) and the importance of the root connections have been demonstrated recently (McCully and Mallet, 1993). The variations in the morphogenetic capacities between maize roots have been studied according to various criteria: live duration (Fusseder, 1987), apical diameter and growth rate (Cahn et al, 1989;Feldmann, 1979), length (Iijima et al, 1991), and anatomy (Jordan et al, 1993;. All these works pointed out the interest of an architectural approach.…”
Section: Introductionmentioning
confidence: 99%